ORGANIZAÇÃO COOPERADA E SOLIDÁRIA DE TRABALHADORES DE MATERIAIS RECICLÁVEIS EM IJUI - Silva, Enio W. d.; Costa, Angela G. d. S.; Silva, Elizandra C. P. d.; Lassen, Manoel F. M.; Berwing, Solange E.; Barcelos, Eronita S.; Basso, Lauri; Rasia, Pedro C.; Frantz, Walter (Salão do Conhecimento, 2013)
Resumo